Partial substitution of herbicides with sorghum allelopathic extract and its impact on productivity of wheat and soil microbes - Devi Lal Kikraliya; U. N. Shukla; Krishna Saharan; A. K. Meena; Moola Ram; R. C. Meena (Brazilian Journal of Microbiology, 2026)

Sustainable wastewater treatments and energy production utilizing microbial fuel cells: A detailed review on advanced technologies - Renuka Devi Ravi; Atul A. Sagade; Abhishek Saxena; Sarojini Devi Nagesh; Rekha Pachaiappan (Desalination, 2026)

Submergence Tolerance in Rice: Genetic Mechanisms, Physiological Adaptations, and Breeding Strategies of Flood Resilience - S. Manju Devi; S. Vignesh; A. John Joel; M. Raveendran; R. Pushpa; R. Suresh (Plant Molecular Biology Reporter, 2026)

Imported Cutaneous Leishmaniasis in India: Diagnosis and Treatment with Implications for Kala Azar Elimination - P. A. Fathima; Manisha Venu; Harish Kumar Shah; K. Devi; Ambooken Betsy; Abdul Salam Sarin; Manju Rahi; Prasanta Saini (Current Microbiology, 2026)

Design, and Synthesis of Donor–π–Acceptor (D–π–A) Heterocyclic Compounds Exhibiting Aggregation-Induced Emission (AIE/AIEE) and Solid-State Emission - Thangjam Linda Devi; Mayanglambam Maneeta Devi; Francis A. S. Chipem; Okram Mukherjee Singh (Journal of Fluorescence, 2026)

Genetic diversity suggests two rather than three larch (Larix spp.) species across Siberia - Marina A. Sheller; Ulf Büntgen; Alexander V. Kirdyanov; Jan Esper; Maria A. Tabakova; Endre György Tóth; Vladimir V. Kukarskih; Alexey I. Kolmogorov; Aleksey A. Ibe; Tatyana V. Sukhikh; Tatiana Bebchuk; Nadezhda Devi; et al. (Perspectives in Plant Ecology, Evolution and Systematics, 2026)

The emerging and escalating consequences of rural depopulation in the Himalaya - Karuna Budhathoki; Bhola Bhattarai; Bed Mani Dahal; Shalini Dhyani; Ambika P. Gautam; Binita Guragain; Dibya Devi Gurung; Muhammad Ismail; Om Katel; Sarala Khaling; Kristina Marquardt; Ulrike Müller-Böker; et al. (Global Environmental Change, 2026)

Planthopper-induced vulnerability: amplifying fall armyworm, Spodoptera frugiperda (J.E. Smith) preference in rice - V. Chinna Babu Naik; S. Rakhesh; D. Devi Pratyusha; K. A. V. Sindhura; Kokkula Akhilesh; K. Vani Sree; R. M. Sundaram (Phytoparasitica, 2026)

Application of bioencapsulated microalgae in marine cladoceran (Penilia sp.) for enhancing growth and improve production of Asian seabass (Lates calcarifer) - K. Nanthini Devi; P. Santhanam; A. Shenbaga Devi; P. Raju; R. Sagaya Princy; K. Rajagopal; I. S. Bright Singh; A. S. Sahul Hameed; A. Jishnu Panamoly; P. Perumal (Journal of Applied Phycology, 2026)

Integrated profiling of drought tolerant rice landraces through comprehensive examination of gene expression, morpho-physiological traits, and biochemical responses during reproductive stage - P. Dharani; T. Nivethitha; S. Manju Devi; A. John Joel (Cereal Research Communications, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Determining Mishmi Hills Farmers Participation in Enhancing Sugarcane Production for Sustainable Livelihood Using PLS-Structural Equation Modeling - Weijimlu Tayang; M. Nirmala Devi; C. Karthikeyan; J. Paul Mansingh; A. Rohini (Sugar Tech, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Growth Parameters, Current Fishery Status and Population Characteristics with Biological Reference Points for Heterocarpus Woodmasoni Alcock, 1901 from Southwestern India - Rekha Devi Chakraborty; A. P. Gayathri; Gyanaranjan Dash; Sreesanth L.; K.T.S Sunil (Thalassas: An International Journal of Marine Sciences, 2026)

Unravelling Ovarian Cancer: an analysis of the Influence of LRP1 and PAI1 Genetic Variations - R. B. Devi Krishna; Sneha Grace Mathews; Preet Agarwal; C. Elizabeth Rani; Nandini Krishnamurthy; Sanjana Murali; A. Lohitha Rani; Leena Dennis Joseph; Banukeerthana Rajasekaran; F. Andrea Mary (Biochemical Genetics, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Novel insecticides and biorationals for managing Noorda blitealis and N. moringae in moringa - M. Duvaraga Devi; M. Muthuswami; A. Suganthi; C. Indu Rani; N. Manikanda Boopathi (International Journal of Tropical Insect Science, 2026)

Comparative Flood Risk Mapping Using Knowledge-Driven, Data-Driven, and Ensemble Models in a Humid Tropical River Basin in India - Chandini Padmanabha Panicker Chandr Senan; Rajendran Shobha Ajin; B. R. Anaswara Devi; A. Rajaneesh; Jitendra K. Nagar; K. S. Sajinkumar (Water Conservation Science and Engineering, 2025)

Unlocking the Potential of Arbuscular Mycorrhizal Fungi: Exploring Role in Plant Growth Promotion, Nutrient Uptake Mechanisms, Biotic Stress Alleviation, and Sustaining Agricultural Production Systems - Ingudam Bhupenchandra; Sunil Kumar Chongtham; Ayam Gangarani Devi; Pranab Dutta; Manas Ranjan Sahoo; Sansuta Mohanty; Sumit Kumar; Anil K. Choudhary; Elangbam Lamalakshmi Devi; Soibam Sinyorita; Soibam Helena Devi; M. Mahanta; et al. (Journal of Plant Growth Regulation, 2025)

Towards sustainable management: growth and population assessment of the deep-sea shrimp Aristeus alcocki Ramadan, 1938, in Southwestern Indian waters - Rekha Devi Chakraborty; Gayathri A. P; Gyanaranjan Dash; G. Maheswarudu; Josileen Jose; P. Laxmilatha; A. P. Dineshbabu; Eldho Varghees; Somy Kuriakose; T. M. Najmudeen; L. Sreesanth; N. Ragesh; et al. (Journal of Coastal Conservation, 2025)

LPCAT3—dependent remodeling of the phospholipids and lipid rafts is essential for vascular proinflammatory signaling and the development of atherosclerosis - Vijay Kondreddy; Jhansi Magisetty; Pranshuta Rawat; Muralidharan Kathirvel; Ramchandra Reddy Jala; B. L. A. Prabhavathi Devi; Sunil K. Singh (Inflammation Research, 2025)

Genomics-assisted stacking of waxy1, opaque2, and crtRB1 genes for enhancing amylopectin in biofortified maize for industrial utilization and nutritional security - Subhra J. Mishra; Firoz Hossain; Rajkumar U. Zunjare; Rashmi Chhabra; Ashvinkumar Katral; Ikkurti Gopinath; Vinay Bhatt; Govinda Rai Sarma; Zahirul A. Talukder; Ravindra K. Kasana; Elangbam L. Devi; Konsam Sarika; et al. (Functional & Integrative Genomics, 2025)

Cognitive neurodynamic approaches to adaptive signal processing in wireless sensor networks - K. G. Shanthi; A. Mary Joy Kinol; S. Rukmani Devi; K. Kannan (Cognitive Neurodynamics, 2025)

Valorization of metabolite-enriched carbohydrates from Theobroma biomass via ultrasound-assisted alkaline extraction - Jose Manuel Núñez-Ramírez; Andrea Martelli; Tabitha Halliday; Bradley Thomas; Corinne Wills; Valeria Cannillo; Devis Bellucci; Carlos Carranza; Paola A. García-Rincón; Piergiorgio Gentile; Joel Girón-Hernández (Carbohydrate Polymers, 2025)

Real-time earthquake magnitude estimation utilizing a mixed dataset set of observed and simulated P-wave onsets for the Kumaon Himalaya from Mw3.0–7.5 earthquakes - Suraj Kumar Pal; S. Devi; Sandeep; P. Kumar; A. Joshi; Monika; R. Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Exploring the genetic potential of cultivated genepool of okra from National Genebank, India - A. Suma; K. Joseph John; M. Latha; P. P. Thirumalaisamy; K. Venkatesan; P. Neeraja; P. P. Gopinath; K. K. Gangopadhyay; Chithra Devi Pandey; Sushil Pandey; P. K. Singh; G. P. Singh (Genetic Resources and Crop Evolution, 2025)

Transforming waste management: leveraging recycletransformernet for effective recycling strategies - A. Devi; Amirtha Saravanan; R. Reeta; V. P. Anitha (Clean Technologies and Environmental Policy, 2025)

Investigation of the high frequency attenuation parameter kappa (κ) beneath the volcanic region of Kyushu using surface and borehole dataset - Sandeep; Sonia Devi; Pragya Singh; U.P. Singh; S.K. Pal; P. Kumar; Monika; A. Kumar; H. Mittal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Regulation of immune-mediated chemoresistance in cancer by lncRNAs: an in-depth review of signaling pathways - Saade Abdalkareem Jasim; Farag M. A. Altalbawy; Subasini Uthirapathy; Ashok Kumar Bishoyi; Suhas Ballal; Abhayveer Singh; Anita Devi; Alexey Yumashev; Yasser Fakri Mustafa; Munther Kadhim Abosaoda (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Investigation of the Optical and Photoluminescence Properties of CaF2: Dy3+ Nanoparticles Synthesized Via Solution Combustion Method for Optoelectronic Applications - N. Sushilal Devi; M. R. Shiekh; L. Raghumani Singh; A. Nabachandra Singh (Journal of Fluorescence, 2025)

Response of foxtail orchid (Rhynchostylis retusa L. Blume.) restoration on various hosts in East Siang district, Arunachal Pradesh - Ruchika Borbaruah; Preeti Hatibarua; Arunkumar Phurailatpam; Sunil Kumar; N. Surmina Devi; Prashant Kisan Nimbolkar; A. S. Mailappa (Plant Ecology, 2025)

Development of a rapid isothermal-based assay for detection of whitefly MEAM1 and MED biotypes using recombinase polymerase amplification - B. Megala Devi; Sivasudha Thilagar; A. Abdul Kader Jailani; Xavier Martini; Mathews L. Paret (Physiology and Molecular Biology of Plants, 2025)

Utilization of genetic diversity and marker trait association to improve anaerobic germination tolerance in rice (Oryza sativa L.)‏ - S. Manju Devi; A. John Joel; M. Raveendran; R. Pushpam; S. Muthuramu; R. Pushpa; N. Sritharan; R. Suresh (Genetic Resources and Crop Evolution, 2025)

Dispersion effectiveness of petroleum oils in low and hypersaline waters - Robyn N. Conmy; Devi Sundaravadivelu; Blake A. Schaeffer; Brian Robinson; Tom King; Robert Grosser (Marine Pollution Bulletin, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluating geostatisical approaches and their integration with pedotransfer functions for estimating the spatial distribution of cation exchange capacity - Farag M. A. Altalbawy; Merwa Alhadrawi; Ashok Kumar Bishoyi; Subbulakshmi Ganesan; Aman Shankhyan; S. Sunitha; Anita Devi; Rajashree Panigrahi; Rubyat Alam (Environmental Monitoring and Assessment, 2025)

Eco-phenological drivers of black gram (Vigna mungo (L) Hepper) productivity in diverse environments and their implications for crop improvement - Ashok K. Parihar; Kali Krishna Hazra; Amrit Lamichaney; Debjyoti Sen Gupta; Anil K. Singh; Jai Dev; Samuel Jaberson; Ajaj A. Lone; S.P. Das; Shayla Bindra; R.K. Panwar; Ashok Kumar; et al. (Field Crops Research, 2025)

Photodegradation of methylene blue from waste water under visible light and bacterial growth inhibition by GO and rGO blended CdO: Mn nanoparticles– a comparative study - N. Manjula; A. R. Balu; B. Sowmiya Devi; S. Chitra Devi; K. Devendran; M. Sriramraj; S. Adityan; A. Vinith (Nanotechnology for Environmental Engineering, 2025)

Biophysical and Biochemical mechanism of plant resistance in Chilli against broad mite, Polyphagotarsonemus latus (Banks) - B. Keerthana; E. Sumathi; M. Murugan; H. Usha Nandhini Devi; M. Duvaraga Devi; A. Senthil (International Journal of Tropical Insect Science, 2025)

Unlocking interfacial effects in NiTiO3-TiO2 eutectic composite: Enhancing overall electrocatalytic and photoelectrochemical water splitting - Sanjit Saha; Assa Aravindh Sasikala Devi; Katarzyna Kolodziejak; Emil Tymicki; Govindan Vadivel; Dorota A. Pawlak (Fuel, 2025)

Remote Sensing Analysis of the LIDAR Drone Mapping System for Detecting Damages to Buildings, Roads, and Bridges Using the Faster CNN Method - S. Meivel; K. Indira Devi; A. Sankara Subramanian; G. Kalaiarasi (Journal of the Indian Society of Remote Sensing, 2025)

Greenhouse gas emission patterns and global warming potential as a result of establishment techniques and nutrient managements in rainfed rice - Keisham Dony Devi; L. Nabachandra Singh; Punabati Heisnam; Edwin Luikham; A. Herojit Singh; N. Gopimohan Singh; Bireswar Sinha; Yengkhom Disco Singh; Toijam Diana; Leitam Chanu Olivia (Paddy and Water Environment, 2025)

Genetic insights of antibiotic resistance, pathogenicity (virulence) and phylogenetic relationship of Escherichia coli strains isolated from livestock, poultry and their handlers - a one health snapshot - Susweta Das Mitra; Rajeswari Shome; Satarupa Bandopadhyay; Sujatha Geddam; A. M. Praveen Kumar; Devi Murugesan; Arijit Shome; Bibek Ranjan Shome (Molecular Biology Reports, 2024)

Dissecting genetic variation for agro-morphological traits of elevated temperature under CO2-temperature gradient chamber and validation of markers linked to heat tolerance of rice (Oryza sativa L.)‏ cultivars of north-eastern Himalayan Region - Amit Kumar; Letngam Touthang; Shankar. P. Das; R. Krishnappa; Avinash Pandey; Arvind Prasad; Shiv Poojan Singh; Simardeep Kaur; C. Aochen; Veerendra Kumar Verma; N. Umakanta; A. Gangarani Devi; et al. (Euphytica, 2024)

Acute Respiratory Syndrome Mimicking Shipping Sickness in Theileria buffeli Infected Buffalo Calf - Varghese Raina; Y. Ajith; Sasi Adithya; S. Anandu; N. Athira; K. S. Athira; P. Preena; K. Vinodkumar; K. Mathew Manju; C. S. Mahima; Jose Akshaya; B. Bruce Alby; et al. (Acta Parasitologica, 2024)

Harmony in nature's elixir: a comprehensive exploration of ethanol and nano-formulated extracts from Passiflora incarnata leaves: unveiling in vitro cytotoxicity, acute and sub-acute toxicity profiles in Swiss albino mice - Balasubramanian Deepika; Pemula Gowtham; Vijayashree Raghavan; Jane Betsy Isaac; Sobita Devi; Venkatakrishnan Kiran; Devadass Jessy Mercy; P. S. Sharon Sofini; A. Harini; Agnishwar Girigoswami; Koyeli Girigoswami (Journal of Molecular Histology, 2024)

Enhancing hoof health and locomotion in crossbred dairy cows: impact of recycled manure solids bedding on lameness incidence and gait kinematics - Selladurai Praveen; Mukund A. Kataktalware; Maharajan Lavanya; Sakhare Abhijeet; Dhaarani Chinnusamy; Sakthivel Jeyakumar; Menon Rekha Ravindra; G. Letha Devi; K. P. Ramesha (Tropical Animal Health and Production, 2024)

Regulation of NS5B Polymerase Activity of Hepatitis C Virus by Target Specific Phytotherapeutics: An In-Silico Molecular Dynamics Approach - Sivaraman Dhanasekaran; Pradeep Pushparaj Selvadoss; Solomon Sundar Manoharan; Srikanth Jeyabalan; Deepak A. Yaraguppi; Abbas Alam Choudhury; V. Devi Rajeswari; Gnanasambandan Ramanathan; Tamilanban Thamaraikani; Mahendran Sekar; Vetriselvan Subramaniyan; Wong Ling Shing (Cell Biochemistry and Biophysics, 2024)

Climatology of thermodynamic indices and background synoptic conditions responsible for severe convection during pre‐ to post‐monsoon seasons over Indian region - A. Madhulatha; M. Mohapatra; K. Sathi Devi; D. R. Pattanaik; M. Rajeevan; Anand Kumar Das; R. K. Jenamani; Naresh Kumar (International Journal of Climatology, 2024)
To investigate the mechanisms responsible for severe convection linked with a variety of mesoscale, synoptic systems over the Indian region, a preliminary analysis is conducted. Using IMD RSRW/Reanalysis (ERA5)/Lightning (TRMM LIS) products both local‐scale thermodynamics and large‐scale background conditions responsible for the major lightning hot spots in different seasons are investigated. In the pre‐monsoon season, high lightning activity over NE Indian region is due to moisture intrusion by south‐westerly at lower levels (warm air advection), along with mid‐level north westerlies (cold air advection) which favour the low‐level convergence and upper‐level divergence. SCS over south India are mainly attributed to wind discontinuity over the region. During monsoon season major lightning activity in NW India is due to the presence of heat low and the rest of the country less intense SCS activity is evident due to high wind shear conditions in connection with low‐level (westerly) and upper‐level (easterly jet stream). In the post‐monsoon season, major lightning in south India are due to the prevailing north‐easterlies and in north India, the activity is attributed to the passage of western disturbance (WD). Station plot analysis suggests the varied distribution of thermodynamic indices season/region‐wise due to the diverse background forcing. Correlation analysis between the lightning and thermodynamic indices suggests that more skillful indices are KI (~0.7 to 0.8), precipitable water (PPW) (~0.8) (pre‐monsoon, monsoon) and (PPW) (~0.8), convective available potential energy (CAPE) (~0.6) in post monsoon over respective lightning hot‐spot regions. Independent verification using Wyoming data/reanalysis for different case studies suggests that monitoring the monthly thresholds of highly correlated indices provides a helpful proxy to operationally forecast the severe convective systems (season/region). Mean Equivalent potential temperature, and mixing ratio in mixed layer has shown reasonable association with the lightning occurrence over all lightning hot spot regions which are implemented in the IMD GFS and IMD WRF models.

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

David versus Goliath: Early career researchers in an unethical publishing system - Aurore Receveur; Jonathan Bonfanti; Stephanie D'Agata; Andrew J. Helmstetter; Nikki A. Moore; Brunno F. Oliveira; Cathleen Petit‐Cailleux; Erica Rievrs Borges; Marieke Schultz; Aaron N. Sexton; Devi Veytia (Ecology Letters, 2024)
The publish‐or‐perish culture in academia has catalysed the development of an unethical publishing system. This system is characterised by the proliferation of journals and publishers—unaffiliated with learned societies or universities—that maintain extremely large revenues and profit margins diverting funds away from the academic community. Early career researchers (ECRs) are particularly vulnerable to the consequences of this publishing system because of intersecting factors, including pressure to pursue high impact publications, rising publication costs and job insecurity. Moving towards a more ethical system requires that scientists advocate for structural change by making career choices that come with risks, many of which disproportionately impact ECRs. We illuminate major issues facing ECRs in Ecology and Evolution under the current publishing system, and propose a portfolio of actions to promote systemic change that can be implemented by ECRs and established researchers.

An investigation on the distribution dynamics of kiddi prawn, Parapenaeopsis stylifera (H. Milne Edwards, 1837) along southwest coast of India, using multi-dimensional approach - Dineshbabu A.P.; Maheswarudu G.; Josileen Jose; Lakshmi Pillai S.; Chakraborty Rekha Devi; Jinesh P.T.; Ragesh N.; Sreesanth L.; Shailaja Salian; Akash S.; Ratheeshkumar R.; Zacharia P.U.; et al. (Regional Studies in Marine Science, 2024)

Positional effect of vortex generators on the combustion efficiency of the micro combustor fuelled with hydrogen/air mixture - P. Booma Devi; Mysoon M. A-Ansari; Nora Dahmash A- Dahmash; M.D Ramesh; H. Aafreen Fathima; Gavurová Beata (Fuel, 2024)

Evaluating the performance of electrocoagulation system in the removal of polystyrene microplastics from water - Akhila Subair; Priya K L; Suchith Chellappan; Thamanna Rahuman A; J. Hridya; P.S. Devi; Mariyam Salkka S; M.S. Indu; Arivalagan Pugazhendhi; Chingakham Chinglenthoiba (Environmental Research, 2024)

Stimulatory effects of seaweed Laminaria digitata polysaccharides additives on growth, immune-antioxidant potency and related genes induction in Rohu carp (Labeo rohita) during Flavobacterium columnare infection - Mohsen Abdel-Tawwab; Ramasamy Harikrishnan; Gunapathy Devi; Eijaz A. Bhat; Bilal A. Paray (Aquaculture, 2024)

Centella asiatica Leaf Extract Mediated One-Pot Green Synthesized rGO Decorated PbS/CdO Nanocomposite for Catalytic Degradation of Methyl Violet from Wastewater and Resistance Against Bacillus subtilis and Pseudomonas aeruginosa Bacterial Strains - M. Suganya; A. R. Balu; S. Chitra Devi; K. Usharani; M. Sriramraj; K. Devendran; S. Adityan (Water, Air, & Soil Pollution, 2024)

Arctic–midlatitude–tropics interactions in January 2020: linkages to precipitation extremes over Indian region - S. D. Sanap; M. Mohapatra; D. R. Pattanaik; S. Sunitha Devi; Satendra Kumar; A. Kashyapi (Meteorology and Atmospheric Physics, 2024)

Toxicological implications of industrial effluents on plants: a review focusing on phytoremediation techniques - A. Hansa; A. Devi; M. Upadhyay; H. Gupta; K. Syam; B. Asgari Lajayer; R. Sharma (International Journal of Environmental Science and Technology, 2024)

Modelling of 1991 Uttarkashi and 2011 Indo-Nepal earthquakes using the modified semi-empirical technique by integrating site-specific quality factor - Monika; Sandeep; Parveen Kumar; Sonia Devi; A Joshi (Journal of Earth System Science, 2023)

Residual Pattern of Chlorantraniliprole, Thiamethoxam, Flubendiamide and Deltamethrin in Tomato Fruit and Soil - Romila Akoijam; Arati Ningombam; Aruna Beemrote; S. S. Roy; Chongtham Sonia; Ch. Premabati Devi; A. Ratankumar Singh; Telem Ratan Singh; H. Nandakumar Singh; Chinglemba Hanglem; I. M. Singh (Bulletin of Environmental Contamination and Toxicology, 2023)

Source and depositional conditions of early Palaeogene coal-bearing sediments, Meghalaya, Eastern India - Sh Priyokumar Singh; Arka Rudra; Y Raghumani Singh; Suryendu Dutta; N Reshma Devi; A Bijayalaxmi Devi; Gyanendra K Trivedi (Journal of Earth System Science, 2023)

First report of natural infection of Capsicum chlorosis virus (Orthotospovirus capsiciflavi) in Capsicum chinense and Capsicum frutescens from jhum groves of North East India - Oinam Priyoda Devi; Susheel Kumar Sharma; Konjengbam Sarda Devi; Nitika Gupta; A. Ratankumar Singh; Subhra Saikat Roy; Richa Rai; Keithellakpam Sanatombi; Virendra Kumar Baranwal (Journal of Plant Pathology, 2023)

New Record of Champsodon Atridorsalis Ochiai & Nakamura, 1964 from the South Eastern Arabian Sea - Rekha Devi Chakraborty; G. Maheswarudu; P. T. Jinesh; N Ragesh; L Sreesanth; Josileen Jose; Pillai S Lakshmi; A P Dineshbabu; Rajendra Naik; T B Retheesh (Thalassas: An International Journal of Marine Sciences, 2023)

Assessment of Lobster Resources in Coastal Region of Gulf of Mannar, Southeast Coast of India - N. Renuga Devi; A. Ahamed Rasheeq; B. Antrose Preethi; Muthusamy Anand; C. Titus; Sankaralingam Subbiah; Kannan Rangesh; R. Dineshkumar; A. Arumugam (Thalassas: An International Journal of Marine Sciences, 2023)

Intraspecific inflorescence and palynological variations in the morphotypes of Amorphophallus paeoniifolius - Shirly Raichal Anil; A. Asha Devi; K. I. Asha; S. Suhara Beevy; E. A. Siril (Genetic Resources and Crop Evolution, 2023)

Sedimentary seagrass carbon stock and sources of organic carbon across contrasting seagrass meadows in Indonesia - Yusmiana P. Rahayu; Mariska A. Kusumaningtyas; August Daulat; Agustin Rustam; Devi D. Suryono; Hadiwijaya L. Salim; Restu N. A. Ati; Nasir Sudirman; Terry L. Kepel; Andreas A. Hutahaean; Novi S. Adi (Environmental Science and Pollution Research, 2023)
Seagrass meadows are an important component of coastal ecosystems globally, and they capture and store organic carbon in living biomass and sediments. Geographical estimates of blue carbon in seagrass habitats are regionally biased, with limited information from the Indo-Pacific region, including Indonesia. Seagrass extent in Indonesia is declining rapidly, and it has been suggested that marine protected areas (MPAs) are an important instrument to support protection of seagrass ecosystems and their services. Thus, this study is aimed at quantifying and comparing sedimentary carbon stocks and sources of organic carbon from seagrass meadows located in undisturbed areas outside MPA, disturbed areas outside MPA, and within MPA in three small islands in Indonesia. The sediment carbon stocks from this study ranged from 19.81 to 117.49 Mg C ha −1 , with the highest stock measured inside MPA (77.15 ± 1.38 Mg C ha −1 ), followed by undisturbed outside MPA (36.08 Mg C ha −1 ), and the lowest stock at disturbed outside MPA (21.86 ± 0.31 Mg C ha −1 ). The predominant source of organic carbon in disturbed meadows was from coastal POM (particulate organic matter, ~ 36%), while in MPA and undisturbed sites, the main source was from seagrass, with ~ 38% and ~ 60% contributions, respectively. The results of this study add more data and information on seagrass blue carbon potential from three different islands with different degrees of disturbance in Indonesia.

Simplified extraction protocol for plant tissues and reverse transcription RPA assay for quick and reliable diagnosis and its application in resistance screening of chilli veinal mottle virus - Huirem Chandrajini Devi; K. Sarda Devi; Rakesh Sanabam; Neeta Pathaw; Oinam Priyoda Devi; Ng. Taibangnganbi Chanu; Albert Maibam; W. Tampakleima Chanu; Jyotsana Sanasam; Subhra Saikat Roy; Ch. Premabati Devi; A. Ratankumar Singh; et al. (Crop Protection, 2023)

Selenium nanomaterial is a promising nanotechnology for biomedical and environmental remediation: A detailed review - M. Sindhu Devi; S. Srinivasan; A. Muthuvel (Biocatalysis and Agricultural Biotechnology, 2023)

Assessment of nest architecture and pollination efficiency of Lasioglossum (Evylaeus) marginatum (Helictidae: Hymenoptera) - Showket A. Dar; Kounser Javeed; Laila A. Al-Shuraym; Samy Sayed; Yendrembam K. Devi; Wajid Hassan; Mohamed Morsi M. Ahmed; Naser A. Alkenani; Ivana Tlak Gajger; James John (Biologia, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Current trends in management of bacterial pathogens infecting plants - Aditi Sharma; A. K. Gupta; Banita Devi (Antonie van Leeuwenhoek, 2023)

Hexagonal nanosheets of pyrrochlore-type lanthanum stannate for sensitive detection of chlorinated pesticide in food and environmental samples - Ramadhass Keerthika Devi; Muthusankar Ganesan; Tse-Wei Chen; Shen-Ming Chen; Rabab Ahmed Rasheed; Wedad A. Al-onazi; Mohamed S Elshikh; Xiaoheng Liu; Jaysan Yu (Food Chemistry, 2023)

Immunostimulatory effect of mannan-oligosaccharides supplementation diet in milkfish (Chanos chanos) - Ramasamy Harikrishnan; Gunapathy Devi; Paramaraj Balamurugan; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Hien Van Doan; Chellam Balasundaram; Simon J. Davies; Ehab El-Haroun (Fish & Shellfish Immunology, 2023)

A sustainable utilization of aquaculture wastewater for the production of commercially important tilapia fish and plants (mint and chickpea) in improved integrated aqua-agriculture system - A. Muhammad Alameen; K. Nanthini Devi; S. Dinesh Kumar; S. Gunabal; N. Krishnaveni; A. Gowthami; S. Sinduja; J. Roopavathy; P. Santhanam; G. Roseline Jebapriya; M. Saranya; A. Aravinth; et al. (Bioresource Technology Reports, 2023)

Modelling of spatial variabilities in the flow structure of a heterogeneous mangrove patch through laboratory scale models - C. A. Lekshmy Devi; P. G. Jairaj; K. Balan (Environmental Fluid Mechanics, 2023)

Effect of Stocking Density on Growth, Water Quality Changes and Cost Efficiency of Butter Catfish (Ompok bimaculatus) during Seed Rearing in a Biofloc System - Snigdha S. Majhi; Soibam Khogen Singh; Pradyut Biswas; Reshmi Debbarma; Janmejay Parhi; Soibam Ngasotter; Gusheinzed Waikhom; Dharmendra Kumar Meena; Ayam Gangarani Devi; Sudhanshu S. Mahanand; K. A. Martin Xavier; Arun Bhai Patel (Fishes, 2023)
Biofloc technology is a modern-day high-density fish culture system employing heterotrophic conversion of nitrogenous waste into useful flocs for water quality control and improved welfare. However, optimization of the stocking density for the target species during seed rearing is the key to a successful farming operation. The study evaluated the effect of different stocking density on the growth, feed utilization, digestive physiology and economics in a biofloc-based seed rearing of butter catfish, O. bimaculatus. Advanced fry (1.21 ± 0.08 g) was reared in a zero-water exchange biofloc system for 90 days at stocking densities of 0.5 g/L(T1), 1.0 g/L(T2), 1.5 g/L(T3) and 2.0 g/L(T4). The observed water quality indicates a reduction in DO and pH in T4, while the total ammonia nitrogen and nitrite levels remained low in T1. Among the groups, highest weight gain was noticed in the lowest stocking density (0.5 g/L) (p

Wheat yield responses to rising temperature: insights from northern plains of India - Philip Kuriachen; Asha Devi; Anu Susan Sam; Suresh Kumar; Jyoti Kumari; A. Suresh; Girish K. Jha (Theoretical and Applied Climatology, 2022)

Assessment of land use and land cover and forest fragmentation in traditional landscape in Manipur, Northeast India - A. R. Devi; T. Shimrah (International Journal of Environmental Science and Technology, 2022)

Genomic insights of beta-lactamase producing Klebsiella quasipneumoniae subsp. similipneumoniae belonging to sequence type 1699 from retail market fish, India - Sudha Sajeev; Muneeb Hamza; Gopalan Krishnan Sivaraman; Sandeep Ghatak; Rakshit Ojha; Suresh Kumar Mendem; Devi Murugesan; Claire Raisen; Bibek R. Shome; Mark A. Holmes (Archives of Microbiology, 2022)

Feature Extraction and Object Detection Using Fast-Convolutional Neural Network for Remote Sensing Satellite Image - N. Bharatha Devi; A. Celine Kavida; R. Murugan (Journal of the Indian Society of Remote Sensing, 2022)

Mercury transportation dynamics in the Ganga Alluvial Plain, India: rainwater–groundwater–river water interaction study from hotspot region - V. Devi; M. M. Atique; A. Raju; G. Upreti; D. K. Jigyasu; J. K. Yadav; S. Singh; R. Kar; M. Singh (International Journal of Environmental Science and Technology, 2022)

Seismic velocity imaging of the Kumaon–Garhwal Himalaya, India - Prantik Mandal; D. Srinagesh; R. Vijayaraghavan; G. Suresh; B. Naresh; P. Solomon Raju; Aarti Devi; K. Swathi; Dhiraj K. Singh; D. Srinivas; Satish Saha; M. Shekar; et al. (Natural Hazards, 2022)

Anti-viral activity of methyl 1-chloro-7-methyl-2-propyl-1h-benzo[d] imidazole-5-carboxylate against white spot syndrome virus in freshwater crab (Paratelphusa hydrodromous) - K. Karthikeyan; A. T. Manish Kumar; D. Harshini; G. Pooja; J. Arul Daniel; Pavani Yasam; G. Gracevictoria; M. Priayanka; P. Krishnaraj; R. Vidya; S. Asha Devi; Sabbasani Rajasekhara Reddy; et al. (Aquaculture International, 2022)

Modelling of 2016 Kumamoto earthquake by integrating site effect in semi-empirical technique - Sonia Devi; Sandeep; Parveen Kumar; Monika; A. Joshi (Natural Hazards, 2022)

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Impact of polystyrene microplastics on major marine primary (phytoplankton) and secondary producers (copepod) - P. Raju; P. Santhanam; S. Sonai Pandian; M. Divya; A. Arunkrishnan; K. Nanthini Devi; S. Ananth; J. Roopavathy; P. Perumal (Archives of Microbiology, 2022)

Gibberellic acids promote growth and exopolysaccharide production in Tetraselmis suecica under reciprocal nitrogen concentration: an assessment on antioxidant properties and nutrient removal efficacy of immobilized iron-magnetic nanoparticles - A. Prathipa; G. Manigandan; S. Dinesh Kumar; P. Santhanam; P. Perumal; N. Krishnaveni; K. Nanthini Devi; S. Vijayalakshmi (Archives of Microbiology, 2021)

Molecular characterization of chikungunya virus isolates from two localized outbreaks during 2014-2019 in Kerala, India - B. Anukumar; T. Asia Devi; Jijo Koshy; N. T. Nikhil; A. P. Sugunan (Archives of Virology, 2021)

Environmental gradients predict the ratio of environmentally acquired carotenoids to self‐synthesised pteridine pigments - Devi Stuart‐Fox; Katrina J. Rankin; Adrian Lutz; Adam Elliott; Andrew F. Hugall; Claire A. McLean; Iliana Medina (Ecology Letters, 2021)
Carotenoids are important pigments producing integument colouration; however, their dietary availability may be limited in some environments. Many species produce yellow to red hues using a combination of carotenoids and self‐synthesised pteridine pigments. A compelling hypothesis is that pteridines replace carotenoids in environments where carotenoid availability is limited. To test this hypothesis, we quantified concentrations of five carotenoid and six pteridine pigments in multiple skin colours and individuals from 27 species of agamid lizards. We show that environmental gradients predict the ratio of carotenoids to pteridines; carotenoid concentrations are lower and pteridine concentrations higher in arid environments with low vegetation productivity. Both carotenoid and pteridine pigments were present in all species, but only pteridine concentrations explained colour variation among species and there were no correlations between carotenoid and pteridine pigments with a similar hue. These results suggest that in arid environments, where carotenoids are likely limited, species may compensate by synthesising more pteridines but do not necessarily replace carotenoids with pteridines of similar hue.

A Review on SARS-CoV-2-Induced Neuroinflammation, Neurodevelopmental Complications, and Recent Updates on the Vaccine Development - Medha Karnik; Narasimha M. Beeraka; Chinnappa A. Uthaiah; Suma M. Nataraj; Anjali Devi S. Bettadapura; Gjumrakch Aliev; SubbaRao V. Madhunapantula (Molecular Neurobiology, 2021)

Red fluorescent ultra-small gold nanoclusters functionalized with signal molecules to probe specificity in quorum sensing receptors in gram-negative bacteria - Anurag M. Chahande; Disha Lathigara; Asmita A. Prabhune; R. Nandini Devi (Archives of Microbiology, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Box–Behnken design and experimental study of ciprofloxacin degradation over Ag2O/CeO2/g-C3N4 nanocomposites - D. Pinheiro; K. R. Sunaja Devi; A. Jose; K. Karthik (International Journal of Environmental Science and Technology, 2021)

Folic Acid as a Bimodal Optical Probe for the Detection of TNT - N. S. Vijila; M. Athira; S. Madanan Anju; A. O. Aswathy; J. Jayakrishna; Mrudula Sreekumar; J. S. Anjali Devi; B. Anjitha; Sony George (Journal of Fluorescence, 2021)

Palynology, palynofacies and organic geochemistry analysis of the late Eocene shale from Meghalaya, Northeast India - N Reshma Devi; Y Raghumani Singh; Mark B Abbott; A Bijayalaxmi Devi (Journal of Earth System Science, 2021)

Education in Ecological Engineering—a Need Whose Time Has Come - Glenn Dale; Gabriela Dotro; Puneet Srivastava; David Austin; Stacy Hutchinson; Peter Head; Ashantha Goonetilleke; Alexandros Stefanakis; Ranka Junge; José A. Fernández L.; Vanessa Weyer; Wayne Truter; et al. (Circular Economy and Sustainability, 2021)
Overcoming Limitations of Ecology and Engineering in Addressing Society’s Challenges By providing an integrated, systems-approach to problem-solving that incorporates ecological principles in engineering design, ecological engineering addresses, many of the limitations of Ecology and Engineering needed to work out how people and nature can beneficially coexist on planet Earth. Despite its origins in the 1950s, ecological engineering remains a niche discipline, while at the same time, there has never been a greater need to combine the rigour of engineering and science with the systems-approach of ecology for pro-active management of Earth’s biodiversity and environmental life-support systems. Broad consensus on the scope and defining elements of ecological engineering and development of a globally consistent ecological engineering curriculum are key pillars to mainstream recognition of the discipline and practice of ecological engineering. The Importance of Ecological Engineering in Society In this paper, the importance of ecological engineering education is discussed in relation to the perceived need of our society to address global challenges of sustainable development. The perceived needs of industry, practitioners, educators and students for skills in ecological engineering are also discussed. The Importance and Need for Ecological Engineering Education The need for integrative, interdisciplinary education is discussed in relation to the scope of ecology, engineering and the unique role of ecological engineering. Scope for a Universally Recognised Curriculum in Ecological Engineering The scope for a universally recognised curriculum in ecological engineering is presented. The curriculum recognises a set of overarching principles and concepts that unite multiple application areas of ecological engineering practice. The integrative, systems-based approach of ecological engineering distinguishes it from the trend toward narrow specialisation in education. It is argued that the systems approach to conceptualising problems of design incorporating ecological principles is a central tenant of ecological engineering practice. Challenges to Wider Adoption of Ecological Engineering and Opportunities to Increase Adoption Challenges and structural barriers to wider adoption of ecological engineering principles, embedded in our society’s reliance on technological solutions to environmental problems, are discussed along with opportunities to increase adoption of ecological engineering practice. It is suggested that unifying the numerous specialist activity areas and applications of ecological engineering under an umbrella encompassing a set of core principles, approaches, tools and way of thinking is required to distinguish ecological engineering from other engineering disciplines and scale up implementation of the discipline. It is concluded that these challenges can only be realised if ecological engineering moves beyond application by a relatively small band of enthusiastic practitioners, learning by doing, to the education of future cohorts of students who will become tomorrow’s engineers, project managers, procurement officers and decision makers, applying principles informed by a growing body of theory and knowledge generated by an active research community, a need whose time has come, if we are to deploy all tools at our disposal toward addressing the grand challenge of creating a sustainable future.

Laboratory investigations on wave attenuation characteristics of Rhizophora Mucronata poir using physical models with bottom friction - C. A. Lekshmy Devi; P. G. Jairaj; K. Balan (Environmental Fluid Mechanics, 2021)

Identification and characterization of a novel long juvenile resource AGS 25 - Sanjay Gupta; Giriraj Kumawat; Soniya Yadav; Rachana Tripathi; Nisha Agrawal; Shivakumar Maranna; Gyanesh K. Satpute; Gireesh Channappa; Mamta Arya; Sayed M. Husain; Virender S. Bhatia; Nanita Devi; et al. (Genetic Resources and Crop Evolution, 2021)

Investigation of Heavy Atom Effect on Fluorescence of Carbon Dots: NCDs and S,N-CDs - A. O. Aswathy; S. Madanan Anju; J. Jayakrishna; N. S. Vijila; J. S. Anjali Devi; B. Anjitha; Sony George (Journal of Fluorescence, 2020)

Influence of weather patterns and air quality on ecological population dynamics of ectoparasites in goats - Y. Ajith; U. Dimri; E. Madhesh; A. Gopalakrishnan; Med Ram Verma; H. A. Samad; K. K. Reena; A. K. Chaudhary; G. Devi; J. Bosco (International Journal of Biometeorology, 2020)

Designing Biomass Rice Husk Silica as an Efficient Catalyst for the Synthesis of Biofuel Additive n-Butyl Levulinate - A. Selva Priya; K. R. Sunaja Devi (BioEnergy Research, 2020)

Spatial variability studies of attenuation characteristics of Qα and Qβ in Kumaon and Garhwal region of NW Himalaya - Monika; Parveen Kumar; Sandeep; Sushil Kumar; A. Joshi; Sonia Devi (Natural Hazards, 2020)

Latitudinal decline in stand biomass and productivity at the elevational treeline in the Ural mountains despite a common thermal growth limit - Frank Hagedorn; Melissa A. Dawes; Maxim O. Bubnov; Nadezhda M. Devi; Andrey A. Grigoriev; Valeriy S. Mazepa; Zufar Y. Nagimov; Stepan G. Shiyatov; Pavel A. Moiseev (Journal of Biogeography, 2020)
Aim To quantify tree biomass and stand productivity of treeline ecotones and identify driving factors. Location treeline ecotones of seven regions from the South to Polar Urals, spanning a latitudinal gradient of 1,500 km. Taxa Picea obovata , Betula pubescens , Larix sibirica. Methods Stand biomass and productivity were estimated across 18 elevational transects from the tree species line to the closed forest line based on allometric measurements of 326 trees (including roots for 53 trees), stand structure assessments and demographic patterns of 20,600 trees. Stand growth data were linked to (a) temperatures monitored in situ for five years in the South and Polar Urals, (b) climate variables extrapolated from nearby climate stations and (c) measures of nutrient availability in soils and tree foliage. Results treeline position along the latitudinal gradient occurred at a similar mean growing season temperature. Despite the common cold limitation of tree distribution along the Ural mountain range, stand biomass and productivity within the treeline ecotone decreased by a factor of three and five from the South to the Polar Urals, mainly due to a declining stand density. Among climatic variables, growing season length decreased by 20% and winter temperatures declined by 4°C towards the Polar Urals, whereas growing degree days > 5°C remained similar, averaging 554 ± 9°C. Soil development was poorer in the Polar than in the South Urals, and plant‐available N and P in the soil were 20 and 30 times lower, respectively, probably due to lower winter temperatures. Main conclusions Our results suggest that once the thermal limitation for tree growth is relieved, soil fertility—restricted by permafrost and low soil temperatures during winter—plays a key and yet underexplored role for stand productivity in treeline ecotones. The observed latitudinal decline in stand productivity is important for above‐ and belowground diversity and functioning.

Efficacy of mating disruption compared with chemical insecticides for controlling Tuta absoluta (Lepidoptera: Gelechiidae) in Kuwait - Mustapha F. A. Jallow; Abdelhafiz A. Dahab; Mohammed S. Albaho; Vimala Y. Devi; Joby Jacob; Omar Al-Saeed (Applied Entomology and Zoology, 2020)

An effective method for extraction of high purity phycocyanins (C-PC and A-PC) from dry biomass of Arthrospira maxima - A. Chandralekha Devi; Hrishikesh A. Tavanandi; K. Govindaraju; K. S. M. S. Raghavarao (Journal of Applied Phycology, 2020)

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

Dissipation Kinetics of Hexaconazole and Lambda-Cyhalothrin Residue in Soil and Potato Plant - Raginee Devi; R. P. Singh; A. K. Sachan (Potato Research, 2019)

Strong motion generation area modelling of the 2008 Iwate earthquake, Japan using modified semi-empirical technique - Sandeep; A Joshi; Sonia Devi; Parveen Kumar; S K Sah; Sohan Lal; Kamal (Journal of Earth System Science, 2019)

Modeling of 2011 IndoNepal Earthquake and Scenario Earthquakes in the Kumaon Region and Comparative Attenuation Study Using PGA Distribution with the Garhwal Region - Sandeep; A. Joshi; S. K. Sah; Parveen Kumar; Sohan Lal; Sonia Devi; Monika (Pure and Applied Geophysics, 2019)

Gene Expression Profiling in Sugarcane Genotypes During Drought Stress and Rehydration - K. Devi; P. T. Prathima; R. Gomathi; R. Manimekalai; K. Lakshmi; A. Selvi (Sugar Tech, 2019)

In silico analysis of the structural and functional implications of SLC19A1 R27H polymorphism - Shaik Mohammad Naushad; Akella Radha Rama Devi; Tajamul Hussain; Salman A. Alrokayan; M. Janaki Ramaiah; Vijay Kumar Kutala (Journal of Genetics, 2019)

Orange-fleshed cucumber (Cucumis sativus var. sativus L.) germplasm from North-East India: agro-morphological, biochemical and evolutionary studies - Pragya Ranjan; Anjula Pandey; A. D. Munshi; Rakesh Bhardwaj; K. K. Gangopadhyay; Pavan Kumar Malav; Chithra Devi Pandey; K. Pradheep; B. S. Tomar; Ashok Kumar (Genetic Resources and Crop Evolution, 2019)

Transformation of waste tin-plated steel to iron nanosheets and their application in generation of oxygen - M. M. Devi; K. N. Ojha; A. K. Ganguli; M. Jha (International Journal of Environmental Science and Technology, 2019)

First detection of Fusarium oxysporum f. sp. cubense tropical race 4 (TR4) on Cavendish banana in India - Raman Thangavelu; D. Mostert; M. Gopi; P. Ganga Devi; B. Padmanaban; A. B. Molina; A. Viljoen (European Journal of Plant Pathology, 2019)

Genetic Status and Endosymbionts Diversity of Bemisia tabaci (Gennadius) on Hosts Belonging to Family Malvaceae in India - T R Hashmi; S R Devi; A Ahmad; N M Meshram; R Prasad (Neotropical Entomology, 2019)

Baseline susceptibility and assessment of resistance risk to flubendiamide and chlorantraniliprole in Tuta absoluta (Lepidoptera: Gelechiidae) populations from Kuwait - Mustapha F. A. Jallow; Abdelhafiz A. Dahab; Mohammed S. Albaho; Vimala Y. Devi; Dawood G. Awadh; Binson M. Thomas (Applied Entomology and Zoology, 2019)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

Simultaneous quantitative monitoring of four indicator contaminants of emerging concern (CEC) in different water sources of Central India using SPE/LC-(ESI)MS-MS - Roshan Appa; V. A. Mhaisalkar; Amit Bafana; S. Saravana Devi; Kannan Krishnamurthi; Tapan Chakrabarti; Pravin K. Naoghare (Environmental Monitoring and Assessment, 2018)

Influence of Diameter Class and Field Conditions on Nutrient Cycling under Toona ciliata M. Roem Trees in North-Western Himalaya - D. R. Bhardwaj; Yogeshwari Devi; Nazir A. Pala; Uday Sharma; Rajesh Kaushal (Environmental Processes, 2018)

Influence of sea grapes (Caulerpa racemosa) supplementation on physical, functional, and anti-oxidant properties of semi-sweet biscuits - Anuj Kumar; Elavarasan Krishnamoorthy; Hanjabam Mandakini Devi; Devananda Uchoi; C. S. Tejpal; George Ninan; A. A. Zynudheen (Journal of Applied Phycology, 2018)

Latitudinal and temporal shifts in the radial growth-climate response of Siberian larch in the Polar Urals - Vladimir V. Kukarskih; Nadezhda M. Devi; Pavel A. Moiseev; Andrey A. Grigoriev; Maksim O. Bubnov (Journal of Mountain Science, 2018)

Heterologous expression of Infectious bursal disease virus VP2 gene in Chlorella pyrenoidosa as a model system for molecular farming - P. Harshavardhan Reddy; A. M. Anthony Johnson; J. Kiran Kumar; T. Naveen; M. Charitha Devi (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

A test of an antipredatory function of conspicuous plastron coloration in hatchling turtles - Beth A. Reinke; Ryan Calsbeek; Devi Stuart-Fox (Evolutionary Ecology, 2017)

Comparative efficacy of alpha-linolenic acid and gamma-linolenic acid to attenuate valproic acid-induced autism-like features - Sneha Yadav; Virendra Tiwari; Manjari Singh; Rajnish K. Yadav; Subhadeep Roy; Uma Devi; Swetlana Gautam; Jitendra Kumar Rawat; Mohd. Nazam Ansari; Abdulaziz Sa Saeedan; Anand Prakash; Shubhini A. Saraf; et al. (Journal of Physiology and Biochemistry, 2017)

Treeline advances and associated shifts in the ground vegetation alter fine root dynamics and mycelia production in the South and Polar Urals - Emily F. Solly; Ika Djukic; Pavel A. Moiseev; Nelly I. Andreyashkina; Nadezhda M. Devi; Hans Göransson; Valeriy S. Mazepa; Stepan G. Shiyatov; Marina R. Trubina; Fritz H. Schweingruber; Martin Wilmking; Frank Hagedorn (Oecologia, 2017)

Developing a biosorbent from Aegle Marmelos leaves for removal of methylene blue from water - S. Baruah; A. Devi; K. G. Bhattacharyya; A. Sarma (International Journal of Environmental Science and Technology, 2017)

Studies on Photocleavage, DNA Binding, Cytotoxicity, and Docking Studies of Ruthenium(II) Mixed Ligand Complexes - Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; N. Deepika; V. Ravi Kumar; P. Venkat Reddy; K Nagasuryaprasad; Surya S. Singh; Penumaka Nagababu; S. Satyanarayana (Journal of Fluorescence, 2016)

Redefining the role of peripheral LPS as a neuroinflammatory agent and evaluating the role of hydrogen sulphide through metformin intervention - Virendra Tiwari; Manjari Singh; Jitendra K. Rawat; Uma Devi; Rajnish K. Yadav; Subhadeep Roy; Swetlana Gautam; Shubhini A. Saraf; Vikas Kumar; Nazam Ansari; Abdulaziz S. Saeedan; Gaurav Kaithwas (Inflammopharmacology, 2016)

Catalase and ascorbate peroxidase—representative H2O2-detoxifying heme enzymes in plants - Naser A. Anjum; Pallavi Sharma; Sarvajeet S. Gill; Mirza Hasanuzzaman; Ekhlaque A. Khan; Kiran Kachhap; Amal A. Mohamed; Palaniswamy Thangavel; Gurumayum Devmanjuri Devi; Palanisamy Vasudhevan; Adriano Sofo; Nafees A. Khan; et al. (Environmental Science and Pollution Research, 2016)

Assessment and comparison of the properties of biodiesel synthesized from three different types of wet microalgal biomass - Katkam N. Gangadhar; Hugo Pereira; Hermínio P. Diogo; Rui M. Borges dos Santos; B. L. A. Prabhavathi Devi; R. B. N. Prasad; Luísa Custódio; F. Xavier Malcata; João Varela; Luísa Barreira (Journal of Applied Phycology, 2016)

Influence of Processing Variables and Storage on the Fruit Drink Developed from Taktir; Wild Fruit of Himalaya - P. Suresh Kumar; V. K. Choudhary; P. Devi; M. Kanwat; A. Sangeetha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Expression and inheritance of chimeric cry2AX1 gene in transgenic cotton plants generated through somatic embryogenesis - A. R. Sakthi; A. Naveenkumar; P. S. Deepikha; N. Balakrishnan; K. K. Kumar; E. Kokila Devi; V. Balasubramani; L. Arul; P. K. Singh; D. Sudhakar; V. Udayasuriyan; P. Balasubramanian (In Vitro Cellular & Developmental Biology - Plant, 2015)

Rival assessment and comparison of morphological and performance-based predictors of fighting ability in Lake Eyre dragon lizards, Ctenophorus maculosus - Claire A. McLean; Devi Stuart-Fox (Behavioral Ecology and Sociobiology, 2015)

Studies on Biosynthesis of Antimicrobial Silver Nanoparticles Using Endophytic Fungi Isolated from the Ethno-medicinal Plant Gloriosa superba L. - Lamabam Sophiya Devi; Donald A. Bareh; S. R. Joshi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Residual behavior and risk assessment of flubendiamide on tomato at different agro-climatic conditions in India - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Sanjay K. Sahoo; N. S. Parihar; B. N. Sharma; V. D. Kale; R. V. Nakat; A. R. Walunj; Saudamini Mohapatra; A. K. Ahuja; Debi Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Treeline advances along the Urals mountain range – driven by improved winter conditions? - Frank Hagedorn; Stepan G. Shiyatov; Valeriy S. Mazepa; Nadezhda M. Devi; Andrey A. Grigor'ev; Alexandr A. Bartysh; Valeriy V. Fomin; Denis S. Kapralov; Maxim Terent'ev; Harald Bugman; Andreas Rigling; Pavel A. Moiseev (Global Change Biology, 2014)
High‐altitude treelines are temperature‐limited vegetation boundaries, but little quantitative evidence exists about the impact of climate change on treelines in untouched areas of Russia. Here, we estimated how forest‐tundra ecotones have changed during the last century along the Ural mountains. In the South, North, Sub‐Polar, and Polar Urals, we compared 450 historical and recent photographs and determined the ages of 11 100 trees along 16 altitudinal gradients. In these four regions, boundaries of open and closed forests (crown covers above 20% and 40%) expanded upwards by 4 to 8 m in altitude per decade. Results strongly suggest that snow was an important driver for these forest advances: (i) Winter precipitation has increased substantially throughout the Urals (~7 mm decade −1 ), which corresponds to almost a doubling in the Polar Urals, while summer temperatures have only changed slightly (~0.05 °C decade −1 ). (ii) There was a positive correlation between canopy cover, snow height and soil temperatures, suggesting that an increasing canopy cover promotes snow accumulation and, hence, a more favorable microclimate. (iii) Tree age analysis showed that forest expansion mainly began around the year 1900 on concave wind‐sheltered slopes with thick snow covers, while it started in the 1950s and 1970s on slopes with shallower snow covers. (iv) During the 20th century, dominant growth forms of trees have changed from multistemmed trees, resulting from harsh winter conditions, to single‐stemmed trees. While 87%, 31%, and 93% of stems appearing before 1950 were from multistemmed trees in the South, North and Polar Urals, more than 95% of the younger trees had a single stem. Currently, there is a high density of seedlings and saplings in the forest‐tundra ecotone, indicating that forest expansion is ongoing and that alpine tundra vegetation will disappear from most mountains of the South and North Urals where treeline is already close to the highest peaks.

Cadmium and copper toxicity in three marine macroalgae: evaluation of the biochemical responses and DNA damage - M. Yokesh Babu; L. Palanikumar; N. Nagarani; V. Janaki Devi; S. Ramesh Kumar; C. M. Ramakritinan; A. K. Kumaraguru (Environmental Science and Pollution Research, 2014)

A comparative study on mesozooplankton abundance and diversity between a protected and an unprotected coastal area of Andaman Islands - Honey U. K. Pillai; K. V. Jayalakshmy; A. Biju; K. J. Jayalakshmi; V. T. Paulinose; C. B. L. Devi; V. R. Nair; C. Revichandran; N. R. Menon; C. T. Achuthankutty; S. U. Panampunnayil (Environmental Monitoring and Assessment, 2014)

Safety evaluation of flubendiamide and its metabolites on cabbage and persistence in soil in different agroclimatic zones of India - K. K. Sharma; Saudamini Mohapatra; A. K. Ahuja; M. Deepa; Debi Sharma; G. K. Jagdish; N. Rashmi; R. S. Battu; S. K. Sharma; Balwinder Singh; N. S. Parihar; B. N. Sharma; et al. (Environmental Monitoring and Assessment, 2014)

Use of nanoclay platelets in food packaging materials: technical and cytotoxicity approach - M. Jorda-Beneyto; N. Ortuño; A. Devis; S. Aucejo; M. Puerto; D. Gutiérrez-Praena; J. Houtman; S. Pichardo; S. Maisanaba; A. Jos (Food Additives & Contaminants: Part A, 2014)

Synthesis, Characterization, DNA Binding Studies, Photocleavage, Cytotoxicity and Docking Studies of Ruthenium(II) Light Switch Complexes - Nazar Mohammed Gabra; Bakheit Mustafa; Yata Praveen Kumar; C. Shobha Devi; A. Srishailam; P. Venkat Reddy; Kotha Laxma Reddy; S. Satyanarayana (Journal of Fluorescence, 2014)

Synthesis and biological evaluation of 1-(3-chloro-2-oxo-4-phenylazetidin-1-yl)-3-(2-oxo-2-(10H-phenothiazin-10-yl)ethyl)urea derivatives - A. Rajasekaran; K. Sheeja Devi (Medicinal Chemistry Research, 2013)

Over-the-Horizon Anomalous VHF Propagation and Earthquake Precursors - M. Devi; A. K. Barbara; Ya. Yu. Ruzhin; M. Hayakawa (Surveys in Geophysics, 2012)

MMP 9 Gene Promoter Polymorphism in Gastric Cancer - D. Krishnaveni; Amar Chand Bhayal; K. Sri Manjari; A. Vidyasagar; M. Uma Devi; M. Ramanna; A. Jyothy; Pratibha Nallari; A. Venkateshwari (Indian Journal of Clinical Biochemistry, 2012)

Multiple shoot induction and regeneration of whole plants from cotyledonary node and nodal explants of Sterculia urens Roxb., a gum yielding tree - P. Subhashini Devi; A. Arundathi; T. Raghava Rao (Journal of Plant Biochemistry and Biotechnology, 2011)

Polyclonal immune responses to antigens associated with cancer signaling pathways and new strategies to enhance cancer vaccines - Timothy M. Clay; Takuya Osada; Zachary C. Hartman; Amy Hobeika; Gayathri Devi; Michael A. Morse; H. Kim Lyerly (Immunologic Research, 2011)

Hemoglobin-derived Peptides as Novel Type of Bioactive Signaling Molecules - Ivone Gomes; Camila S. Dale; Kimbie Casten; Miriam A. Geigner; Fabio C. Gozzo; Emer S. Ferro; Andrea S. Heimann; Lakshmi A. Devi (The AAPS Journal, 2010)

Economic analysis of risk of gastrointestinal parasitic infection in cattle in North Eastern States of India - S. Bandyopadhyay; S. Mandal; K. K. Datta; P. Devi; S. De; A. K. Bera; D. Bhattacharya (Tropical Animal Health and Production, 2010)

Geospatial modelling for identification of potential ecological corridors in Orissa - A. Roy; B. S. S. Devi; B. Debnath; M. S. R. Murthy (Journal of the Indian Society of Remote Sensing, 2010)

Anomalous total electron content (TEC) and atmospheric refractivity prior to the very strong China earthquake of May 2008 - M. Devi; A. K. Barbara; A. H. Depueva; Y. Y. Ruzhin; V. Depuev (International Journal of Remote Sensing, 2010)

Multiplex PCR for identification of parasitic eggs of Oesophagostomum spp. Isolated from sheep and goat - S. Bandyopadhyay; S. Naskar; P. Devi; A. K. Bera; S. De; D. Pan; T. Rana; S. Das; S. Sikdar; D. Bhattacharya (Proceedings of the Zoological Society, 2009)

Increased vincristine production from Agrobacterium tumefaciens C58 induced shooty teratomas of Catharanthus roseus G. Don - Fathimunnisa Begum; S.S.S. Nageswara Rao; Kiranmayee Rao; Y. Prameela Devi; A. Giri; C.C. Giri (Natural Product Research, 2009)

Age-related responses of the rat cerebral cortex: influence of vitamin E and exercise on the cholinergic system - A. B. Jolitha; M. V. V. Subramanyam; S. Asha Devi (Biogerontology, 2009)

Treatment with bindarit, an inhibitor of MCP-1 synthesis, protects mice against trinitrobenzene sulfonic acid-induced colitis - M. Bhatia; C. Landolfi; F. Basta; G. Bovi; R. Devi Ramnath; A. Capezzone de Joannon; A. Guglielmotti (Inflammation Research, 2008)

Cannabinoid CB2 Receptor-Mediated Anti-nociception in Models of Acute and Chronic Pain - Maulik D. Jhaveri; Devi R. Sagar; Steven J. R. Elmes; David A. Kendall; Victoria Chapman (Molecular Neurobiology, 2007)

Targeting opioid receptor heterodimers: Strategies for screening and drug development - Achla Gupta; Fabien M. Décaillot; Lakshmi A. Devi (The AAPS Journal, 2006)

G protein coupled receptor dimerization: implications in modulating receptor function - Ivone Gomes; Bryen A. Jordan; Achla Gupta; Carl Rios; Nino Trapaidze; Lakshmi A. Devi (Journal of Molecular Medicine, 2001)

Culture and regeneration of mesophyll-derived protoplasts of sorghum [ Sorghum bicolor (L.) Moench] - R. V. Sairam; N. Seetharama; P. S. Devi; A. Verma; U. R. Murthy; I. Potrykus (Plant Cell Reports, 1999)